PENILAIAN PROFESIONALISME ADVOKAT DALAM PENEGAKAN HUKUM MELALUI PENGUKURAN INDIKATOR KINERJA ETISNYA - Raharjo, Agus; Sunarnyo, Sunarnyo (Jurnal Media Hukum, 2014)
The range of advocates work happens from investigation to law enforcement. The scope of the extensive works as a guard puts a major advocate in the resolution of the criminal case. The strategic position of the advocate and the pressure to win every case has caused most advocates take disgraceful behavior to achieve goals. Advocate profession as a real respectable profession (officium nobile) stained by the act of advocate it self. Personal commitment to uphold professional ethics in the performance of duties is not supported by an adequate level of supervision. Indeed, in the field of work, advocates have independence, but in relation to professional ethics they are under control of supervisor commission established by the advocate organization. According to what we need the supervision maximized through ethical assessment of performance indicators. This article will explain what ethical performance indicators are and their assessment of informants who become the object of research.